PENGARUH MOTIVASI BERPRESTASI DAN PERILAKU KOMUNIKASI ANTARPRIBADI TERHADAP EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH: (Survei terhadap Kepala SMP di Provinsi Sulawesi Tenggara) - Hartono, Abdul Nashir (Perspektif Ilmu Pendidikan, 2007)
This survey is aiming to analyse the effect of achievement motivation and interpersonal communication attitude towards the effectiveness of principal leadership both individually and in batches. The result of survey indicates that the effectiveness of principal leadership is predicted to be improved; achievement motivation and interpersonal communication attitude of principals must be stimulated intensively. The stimulus is intended to create a condition where the principals have chances to gain high achievement motivation and a positive communication attitude. In order to improve achievement motivation, it is recommended that promotion to be a principal is not a termination of a carrier, to make inventory, documentation and publication of achievement values, and to give achievement motivation test to principal candidates. To create positive interpersonal communication attitude, it is necessary to give them a kind of interpersonal communication training. At the same time, school management laboratory is needed to facilitate the improvement of those independent variables simultaneously besides helping principals to overcome some problems dealing with decentralization.